Fabrication of electroactive poly(vinylidene fluoride) through non-isothermal crystallization and supercritical CO2 processing. Issue 77 (17th October 2017) - Lee, Ji Eun; Guo, Yanting; Lee, Richard Eungkee; Leung, Siu Ning
Abstract : A new strategy using non-isothermal crystallization and supercritical CO2 processing is found to promote the electroactive phase content in PVDF. Abstract : Poly(vinylidene fluoride) (PVDF) with enhanced β phase content has conventionally been manufactured by mechanical stretching and electric poling of PVDF films. More recently, scientific research has been conducted to investigate the use of electrospinning to promote the piezoelectric properties of PVDF. In this work, we developed a novel processing strategy using a combination of non-isothermal crystallization and supercritical carbon dioxide (ScCO2 ) processing to promote the electroactive ( i.e., β and γ) phase content of PVDF. Differential scanning calorimetric, X-ray diffraction, and infrared spectroscopy results revealed that the preferential formation of β and γ crystal phases were induced by the ScCO2 foaming step and the non-isothermal crystallization step, respectively. The sequential crystallization of these electroactive phases were coupled by their relationships with the ScCO2 -induced foam expansion. Furthermore, both ScCO2 's plasticization effect and annealing helped the promotion of PVDF's degree of crystallinity. Overall, this work offers a new industrially viable methodology to tailor PVDF's crystalline structures. This represents a useful technique to fabricate piezoelectric PVDF film for sensors, actuators, and energy harvesting applications.